2022
DOI: 10.5194/soil-8-319-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of catena position and hydrology on soil chemical weathering

Abstract: Abstract. The sensitivity of chemical weathering to climatic and erosional forcing is well established at regional scales. However, soil formation is known to vary strongly along catenas where topography, hydrology, and vegetation cause differences in soil properties and, possibly, chemical weathering. This study applies the SoilGen model to evaluate the link between the topographic position and hydrology with the chemical weathering of soil profiles on a north–south catena in southern Spain. We simulated soil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…We attribute this difference to the weak soil moisture seasonality in our study sites (Fig. 4), typical in tropical páramo ecosystems (Mosquera et al, 2022), which results in small ranges (max-min) of soil moisture for cushion plants (≤ 0.09 cm 3 cm -3 ) and tussock grasses (≤ 0.07 cm 3 cm -3 ) in comparison with larger soil moisture ranges from the modeled soil profiles (0.35 cm 3 cm -3 ) (Cipolla et al, 2021;García-Gamero et al, 2022).…”
Section: The Effect Of Vegetation On Contemporary Soil Weathering Thr...mentioning
confidence: 83%
See 2 more Smart Citations
“…We attribute this difference to the weak soil moisture seasonality in our study sites (Fig. 4), typical in tropical páramo ecosystems (Mosquera et al, 2022), which results in small ranges (max-min) of soil moisture for cushion plants (≤ 0.09 cm 3 cm -3 ) and tussock grasses (≤ 0.07 cm 3 cm -3 ) in comparison with larger soil moisture ranges from the modeled soil profiles (0.35 cm 3 cm -3 ) (Cipolla et al, 2021;García-Gamero et al, 2022).…”
Section: The Effect Of Vegetation On Contemporary Soil Weathering Thr...mentioning
confidence: 83%
“…In contrast, Cipolla et al, (2021) found a hysteric relationship between soil moisture and weathering rates in a short-term study and attributed this non-linearity to a memory of past events (wet and dry periods). -Gamero et al, (2022) found a positive relationship between soil moisture and soil weathering using a long-term model. We attribute this difference to the weak soil moisture seasonality in our study sites (Fig.…”
Section: The Effect Of Vegetation On Contemporary Soil Weathering Thr...mentioning
confidence: 90%
See 1 more Smart Citation
“…For example, a drier climate is predicted for Central America (Hidalgo et al, 2013). This could exaggerate the comparative lack of soil water on upper slopes (García-Gamero et al, 2021), which, in turn, can affect nutrient availability (Marschner and Rengel, 2012; Viets, 1967). In particular, soil water is known to affect the availability of the key element phosphorus (O’Connell et al, 2018), and therefore possibly the distributions of species sensitive to phosphorus, along the topographic gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Soil water availability can be approached using the ratio of mean annual rainfall to potential evapotranspiration, as illustrated in studies of soil development along climatic gradients (Chadwick et al, 2003;Dixon et al, 2016;Schoonejans et al, 2016) and at the global scale (Calabrese and Porporato, 2020). While these investigations have recognized the importance of water flux and transport in soil weathering, only a few of them have directly assessed how soil water fluxes (Clow and Drever, 1996;Maher, 2010;White et al, 2009) and hydrological processes, like infiltration and storage (Cipolla et al, 2021;García-Gamero et al, 2022), control weathering processes. Moreover, the effect of the water balance on soil weathering can be elusive due to the potential influence of less-explored co-evolving soil formation factors, notably lithological and climatic settings (Schoonejans et al, 2016).…”
Section: Introductionmentioning
confidence: 99%